2007
DOI: 10.1111/j.1462-2920.2007.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes involved in the biosynthesis of the cytotoxic compound glidobactin from a soil bacterium

Abstract: Glidobactins (syn. cepafungins) are a family of structurally related cytotoxic compounds that were isolated from the soil bacterial strain K481-B101 (ATCC 53080; DSM 7029) originally assigned to Polyangium brachysporum and, independently, from an undefined species related to Burkholderia cepacia. Glidobactins are acylated tripeptide derivatives that contain a 12-membered ring structure consisting of the two unique non-proteinogenic amino acids erythro-4-hydroxy-l-lysine and 4(S)-amino-2(E)-pentenoic acid. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
99
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 37 publications
1
99
0
4
Order By: Relevance
“…SylA is produced in vivo by a nonribosomal peptide synthetase, which is constituted by an array of enzymes responsible for attachment of amino acid building blocks and introduction of chemical modifications. SylD, a 460-kDa multidomain enzyme, represents the major part of this assembly line and was chosen for BLAST alignment (17,18). The search yielded hits among various Photorhabdus and Burkholderia species, which can therefore be suggested to produce analogous natural products.…”
Section: Resultsmentioning
confidence: 99%
“…SylA is produced in vivo by a nonribosomal peptide synthetase, which is constituted by an array of enzymes responsible for attachment of amino acid building blocks and introduction of chemical modifications. SylD, a 460-kDa multidomain enzyme, represents the major part of this assembly line and was chosen for BLAST alignment (17,18). The search yielded hits among various Photorhabdus and Burkholderia species, which can therefore be suggested to produce analogous natural products.…”
Section: Resultsmentioning
confidence: 99%
“…Syrbactins are natural products that share biosynthetic pathways by related gene clusters (16,17). They exhibit an ␣,␀-unsaturated carbonyl system located within a macrocycle that reacts irreversibly with the proteasomal active site Thr1O ␄ by a Michael-type 1,4-addition.…”
mentioning
confidence: 99%
“…This fragment was used to isolate the complete gene cluster from DSM 7029 ( Figure 2B). Insertion mutants confirmed that this cluster encoded the glidobactin A synthetase (Schellenberg et al, 2007). This analysis suggests that B. pseudomallei and P. luminescens are able to produce glidobactin-like compounds.…”
Section: Syringolin A-like Molecules In Other Bacterial Speciesmentioning
confidence: 66%